Forced displacement in the context of the adverse effects of climate change and conflict. Global trends: Forced displacement in 2023 - Alliance of Bioversity International and International Centre for Tropical Agriculture (2024)
The latest Global Trends report, published in June 2024, provides key statistical trends on forced displacement. It includes the latest official statistics on refugees, asylum-seekers, internally displaced and stateless people, as well as the number of refugees who have returned home.